(3QSGdI aj Gdabgs - (3GHf eGfY , eMeO Hf YHO GdYRjR Hf eMeO Hf YHO Gddg Hf eMeO Hf EHQGgje Hf eGfY Hf THQeI Gdhgjfj,J (B1385 (3g` s
(3ChdgG (B:s
(3ef YHO GdYRjR Hf eMeO Hf eGfY Edi LfGH GdecQe GdCN GdTjN YHO Gddg Hf eMeO Hf ONjd MaXg Gddg JYGdi hHYO abO HdZfG JTfjYc Ydi CNjc hgPG CNj djS ef Odjg s
(3BNQgG (B:s
(3hJbhd eG jJUhQ gPG EdG HGdEfMfGA hJLYdg ef GdeSJMjd agPG djS HLhGH hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi eMeO hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B209s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs